2002
DOI: 10.1038/sj.sc.3101280
|View full text |Cite
|
Sign up to set email alerts
|

Spinal injuries resulting from horse riding accidents

Abstract: Injuries sustained as a result of horse riding are common. Serious injuries to the nervous system are the most dangerous. An analysis has been made of 11 papers, new ®gures produced by surveying Stoke Mandeville, Oswestry and Odstock spinal units and by searching the internet to determine their frequency and distribution. Head injuries outnumber spinal injuries by ®ve to one. In contrast to other sporting accidents, there are more lumbar and thoracic than cervical injuries and more women are injured than men (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 13 publications
2
46
1
5
Order By: Relevance
“…Another German study about fatal horse riding accidents showed that next to craniocerebral trauma, thoracolumbar spine fractures were the most commonly encountered injury in all fatalities with an overall incidence of 10% [18]. Several other studies confirmed that 7-10% of all riders requiring hospital admission will have a spinal injury [14,[22][23][24][25].…”
Section: Spine Fracturesmentioning
confidence: 82%
“…Another German study about fatal horse riding accidents showed that next to craniocerebral trauma, thoracolumbar spine fractures were the most commonly encountered injury in all fatalities with an overall incidence of 10% [18]. Several other studies confirmed that 7-10% of all riders requiring hospital admission will have a spinal injury [14,[22][23][24][25].…”
Section: Spine Fracturesmentioning
confidence: 82%
“…They tend to be associated with inexperience and poor knowledge of the inherent dangers of the sport, inadequate coaching and practice facilities, lack of supervision, protective equipment and strict refereeing [2,22]. Cantu et al [3] reported how teaching the fundamental techniques of the game, equipment standards, and improved medical care both on and off the playing field led to an amazing 270% reduction in permanent spinal cord injury in American football.…”
Section: Discussionmentioning
confidence: 99%
“…Body areas with the highest number of responses were the ankles (99), knees (108) and hips (49). Body areas with the lowest number of responses were the tibia/fibula (5), forearm (6) and humerus (1). Shoulder/humeral data is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1,2,3, 4 Silver reported "horse-riders can expect a serious accident once in every 350 hours of participation, which is twenty times more dangerous than motor cycling." 1 The head was the most commonly injured body part amongst riders 19-49, with upper extremity fractures just ahead of concussion (16.6 vs. 15.2%) in riders' age 0-18. 5 High incidences of orthopedic injuries have been reported in several populations of riders less than 25 years of age.…”
Section: Introductionmentioning
confidence: 99%